Manajemen proyek I. Dari konseptual sampai operasional. Konsep, studi kelayakan dan ... - SOEHARTO, Iman (Erlangga, 1999)
Manajemen proyek I. Dari konsepyual sampai operasional. Konsep, studi kelayakan dan